2009
DOI: 10.1172/jci37131
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility loci for murine HIV-associated nephropathy encode trans-regulators of podocyte gene expression

Abstract: Multiple studies have linked podocyte gene variants to diverse sporadic nephropathies, including HIV-1-associated nephropathy (HIVAN). We previously used linkage analysis to identify a major HIVAN susceptibility locus in mouse, HIVAN1. We performed expression quantitative trait locus (eQTL) analysis of podocyte genes in HIV-1 transgenic mice to gain further insight into genetic susceptibility to HIVAN. In 2 independent crosses, we found that transcript levels of the podocyte gene nephrosis 2 homolog (Nphs2), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 70 publications
5
79
0
Order By: Relevance
“…The importance of HIV RNA in the development of HIVICK has been suggested by the failure to generate this entity in experimental models. Contrary to HIVAN, in which many HIV-1 transgenic models exhibit the clinical and pathologic features of HIVAN, none of these animal models exhibit features of HIVICK (28,29). This observation suggests that viral replication or immune responses to viral proteins may be essential to trigger HIVICK (30).…”
Section: Discussionmentioning
confidence: 90%
“…The importance of HIV RNA in the development of HIVICK has been suggested by the failure to generate this entity in experimental models. Contrary to HIVAN, in which many HIV-1 transgenic models exhibit the clinical and pathologic features of HIVAN, none of these animal models exhibit features of HIVICK (28,29). This observation suggests that viral replication or immune responses to viral proteins may be essential to trigger HIVICK (30).…”
Section: Discussionmentioning
confidence: 90%
“…Elucidation of the reasons for the distinct difference in susceptibility to Tns2-deficiency among renal disease due to podocyte-specific knockout of tetraspanin CD151, whereas B6 strain is generally resistant to experimental glomerular disease, including HIV-associated nephropathy and adriamycininduced nephropathy (16)(17)(18). Like Cd151, Tns2 interacts with integrins and its deficiency leads to alterations in the podocyte foot processes (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard and similar to humans, genetic susceptibility has a profound effect on the development of nephropathy in the HIV-1 transgenic mouse model: the FVB/NJ strain is very susceptible, but F1 hybrids with BALB/cJ, C57BL/6J and CAST/EiJ are protected. 17,18 Taking advantage of this strain dependence, we previously generated mapping cohorts between TgFVB and two counterstrains (C57BL/6J and CAST/EiJ strains), leading to identification of nephropathy quantitative trait loci (QTLs) on chromosomes 3, 13, and 4 (HIVAN1, HIVAN2, and HIVAN3 loci, respectively). 17,18 Further examination of these loci with expression QTL analysis (expression profiling combined with linkage analysis) showed that the HIVAN1 and HIVAN2 loci regulate expression of Nphs2 (encoding Podocin) and several other podocyte-expressed genes.…”
mentioning
confidence: 99%
“…17,18 Taking advantage of this strain dependence, we previously generated mapping cohorts between TgFVB and two counterstrains (C57BL/6J and CAST/EiJ strains), leading to identification of nephropathy quantitative trait loci (QTLs) on chromosomes 3, 13, and 4 (HIVAN1, HIVAN2, and HIVAN3 loci, respectively). 17,18 Further examination of these loci with expression QTL analysis (expression profiling combined with linkage analysis) showed that the HIVAN1 and HIVAN2 loci regulate expression of Nphs2 (encoding Podocin) and several other podocyte-expressed genes. 18 These data indicated the HIVAN1 and HIVAN2 susceptibility genes belong to a common regulatory pathway, and they likely introduce genetic lesions in an expression network involving multiple human nephropathy genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation